About the Project Approach Implementation in Public Administration and Local Self-Government - V. V. Yanovskiy; A. P. Isaev; A. K. Nescheret (Управленческое консультирование)
The absence within the framework of targeted programs (state, local) of a project mechanism defining the final product, the timing of its achievement using the established framework of budget financing, washes out the essence of these programs. Often they are formal and their implementation is reduced to the implementation of “measures”, the feasibility of which is notobvious. And complex interdepartmental projects often “slip” due to the lack of proper level and quality of communications in its implementation by reason the project manager privation with parts of authority.Apparently, the implementation of the project approach in local government bodies is even more relevant, where the result of the work is assessed not only by higher authorities and controlling bodies but also by real inhabitants. Our paper considers the main features of applying the project management principles in the executive bodies of public management and the required competencies of the project office head, key roles and functions office employees when implementing the project approach..The analysis carried out by the authors in many respects of the pioneering practice of the Leningrad Region made it possible to identify the main problems of the project management implementation and ways of overcoming them for the subjects of theRussian Federation, the necessary personal and managerial competencies of personnel involved in project management. The implementation of a large-scale digital technological transformation developed in a single federal center for modern services will allow optimizing the timing of the project task solutions, as was shown